Human and animal morbillivirus strains causing chronic neurological infections share key genotypic and phenotypic traits - Melvin Daniel Roji; Franziska Geiselhardt; Georg Beythien; Kristin Laudeley; Monica Mirolo; Wendy K. Jo; Laura Martino; Andreas Beineke; Wolfgang Baumgärtner; Martin Peters; Judith M. A. van den Brand; Trine H. Jensen; et al. (Proceedings of the National Academy of Sciences, 2026)
Long-term persistent measles virus (MeV) infection of the central nervous system (CNS) can result in subacute sclerosing panencephalitis (SSPE), an invariably fatal late neurological complication of measles. Analogous SSPE-like chronic diseases have also been reported in adult dogs, cetaceans, and more recently harbor seals following infection by canine distemper virus (CDV), dolphin morbillivirus (DMV), and phocine distemper virus (PDV), respectively. Here, we characterize different animal morbilliviruses (CDV lynx , PDV 2001 , PDV 2014 , and DMV 232-18 ) that persisted in the CNS of their respective host species for several years after the initial infections. The CDV lynx and DMV 232-18 strains encode nonfunctional matrix proteins and hyperfusogenic fusion proteins which are hallmark features of SSPE MeV strains. The complex mutational profile apparent in the PDV 2001 strain also has parallels with MeV strains from SSPE cases. In contrast, the PDV 2014 strain encodes for a nonfunctional matrix protein but an unmodified F protein supporting the evolutionary precedence of M protein changes in facilitating long-term morbillivirus infections of the CNS. Consequently, our findings show that similar evolutionary pathways across different animal species drive morbilliviruses to evolve analogous mechanisms favoring virus persistence in the CNS and the development of chronic neurological disease. Such naturally occurring chronic animal morbillivirus infections of the CNS provide natural analogues for studying the evolutionary trajectory and molecular basis of the pathogenesis of SSPE in humans. This may pave the way for developing early diagnostics and intervention strategies.